ZEB1‐AS1: A crucial cancer‐related long non‐coding RNA. (10th December 2017) - Li, Jinglin; Li, Zhenglong; Leng, Kaiming; Xu, Yi; Ji, Daolin; Huang, Lining; Cui, Yunfu; Jiang, Xingming
Abstract: Long non‐coding RNAs (lncRNAs) recently emerge as a novel class of non‐coding RNAs (ncRNAs) with larger than 200 nucleotides in length. Due to lack an obvious open reading frame, lncRNAs have no or limited protein‐coding potential. To date, accumulating evidence indicates the vital regulatory function of lncRNAs in pathological processes of human diseases, especially in carcinogenesis and development. Deregulation of lncRNAs not only alters cellular biological behavior, such as proliferation, migration and invasion, but also represents the poor clinical outcomes. Zinc finger E‐box binding homeobox 1 antisense 1 (ZEB1‐AS1), an outstanding cancer‐related lncRNA, is identified as an oncogenic regulator in diverse malignancies. Dysregulation of ZEB1‐AS1 has been demonstrated to exhibit a pivotal role in tumorigenesis and progression, suggesting its potential clinical value as a promising biomarker or therapeutic target for cancers. In this review, we make a summary on the current findings regarding the biological functions, underlying mechanisms and clinical significance of ZEB1‐AS1 in cancer progression.